Christmas cupcake murder [compact disc, unabridged] - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2020)
While Hannah speeds through a lengthy holiday checklist, drama in town grows like Santa's waistline on Christmas Eve. Her sister Andrea wants to stave off the blues by helping out at The Cookie Jar, Michele's love life is becoming complicated, Lisa needs Hannah's advice, and Delores has a Christmas secret she's not willing to share. But nothing dampens the holiday mood more than the chilling mystery surrounding the man found near death in an abandoned storefront two doors down from Hannah's bakery.